Anspruch : 1980-1990 Galerie Walzinger. - Fiedler-Bender, Gisela; Holeczek, Bernhard; Galerie Walzinger, Saarlouis (Saarlouis : Galerie Walzinger, 1990)
Badur, Frank ; Böhm, Hartmut ; Bonies, Bob ; Erb, Leo ; Frietzsche, Georg ; Girke, Raimund ; Hangen, Heijo ; Huwer, Hans ; Kaminsky, Thomas ; Maltz, Russell ; McCarty, John ; Mosley, Tom ; Niemeyer, Jo ; Niestrath, Eva ; Pahle, Achim ; Reichert, Jürgen ; Steinmann, Klaus ; Verhaegen, Dirk ; Williams, Mark
Zehn Jahre Galerie Walzinger
boek